ADAPT AND OVERCOME: REVISING US NAVAL DOCTRINE AND POLICY IN AN ERA OF UNCONVENTIONAL CONFLICT - Lowther, Adam B. (Scientia Militaria - South African Journal of Military Studies, 2011)
When the Quadrennial Defense Review (QDR) was released in Februaryof 2006, the United States was in the middle of a multi-front Global War on Terror(GWOT) that had been underway for more than four years. Beginning with theinitial response to the 9/11 attacks in October of 2001, the US Navy began to play asignificant part in the unconventional operations that characterised the early days ofOPERATION ENDURING FREEDOM. While the Navy carried out its missionadmirably supporting Special Operations Forces (SOF) by providing the USS KittyHawk (CV 63) as a “lily pad”, which enabled Rangers, Delta operators, GreenBerets, and SEALs to move in and out of Afghanistan from a maritime staging area,it was a role well outside the norm of American naval operations and one the Navyis yet to fully embrace.